Financial Literacy Skills as an Effort to form Smart Character in Managing Finances in Karya Utama High School Students - Saputri, Khana; Agustina; Katharina, Ninta; Amir, Afriza; Agung Anggoro, Muhammad; Fitriano, Andre (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Financial Literacy is knowledge, skills and beliefs that influence attitudes and behavior to improve the quality of decision making and financial management to achieve community welfare. Implementing financial education in order to increase public financial literacy is very necessary because based on a survey conducted by the OJK in 2022, the financial literacy index of the Indonesian population is 49.68 percent, an increase compared to 2013, 2016 and 2019 which were only 21.84 percent each. , 29.70 percent, and 38.03 percent. Service activities were carried out at Karya Utama Private High School Jl. Education No. 23 Marindal Satu, Patumbak District, Deli Serdang Regency, North Sumatra was held on May 20 2024. This activity is a form of socialization and special training for students of Karya Utama Private High School Jl. Education No. 23 Marindal Satu, Patumbak District, Deli Serdang Regency, North Sumatra so that they can have financial literacy skills as an effort to build intelligent character in managing finances in Karya Utama High School students.